Recent Advances in Application of Poly-Epsilon-Caprolactone and its Derivative Copolymers for Controlled Release of Anti-Tumor Drugs - Sun, Zhiqiang; Duan, Ranglong; Xing, Dejun; Pang, Xuan; Li, Zhiying; Chen, Xuesi (Current Cancer Drug Targets, 2017)
Background: Due to their excellent biocompatibility and biodegradability, poly-epsiloncaprolactone and its derivative copolymers have been extensively studied as drug carriers in pharmaceutical and medical fields, especially for controlled release of anti-tumor drugs. Poly-epsiloncaprolactone based drug delivery systems lead to major advantages including uniform drug distribution, long term of degradation and drug release process, non-toxic in nature and cyto-compatible with body tissues. Approved by US Food and Drug Administration, poly-epsilon-caprolactone provides a promising platform for design and fabrication of anti-tumor drug delivery systems with controllable drug release behaviors. Methods: This mini-review focused on the recent progress in application of poly-epsiloncaprolactone based materials for controlled release of cancer therapy drugs. A careful search was performed on web of science, mainly focused on the related papers published from 2013 to 2016. Conclusion: Recent advances in applying poly-epsilon-caprolactone for controlled delivery and targeting release of chemical anti-tumor drugs were summarized in this mini-review. Benefited from the efforts of scientists all over the world, various chemotherapeutic drug delivery systems based on different formulations of poly-epsilon-caprolactone related materials have been evaluated. It has been widely recognized that the introduction of of poly-epsilon-caprolactone components into drug delivery systems would increase drug loading capacity, decrease leakage, prolong releasing period and result in controllable releasing rate. Especially with the development of environment-responsive delivery systems (pH-, thermo-, magnetic field- and light-responsive drug carriers), enhanced tumor cell targeting potential, as well as decreased systemic toxicity would be realized.
Keywords: controlled release